A percepção da comunidade acadêmica da Unipampa Uruguaiana, em relação ao saneamento no campus - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This work is a research on the knowledge of users at the Federal University of Pampa - UNIPAMPA, campus Uruguaiana, about basic sanitation on campus, more specifically on the quality of water collected and made available to users, and on the correct destination waste on campus, among other pertinent matters. The survey took place in a questionnaire format, using Google Forms as a methodological resource, an online platform that provides access to responses in real time and also allows for anonymous responses. A negative point to be mentioned noticed in this survey was the low adherence of respondents to the survey, perhaps even due to the lack of interest in discussing the topic. After analyzing the graphs generated from the distribution of responses, by the Google platform itself, it can be believed that the lack of discussion of the topic at the university is due to several determining factors, among which the lack of knowledge of the users about water quality and the correct disposal of sewage, due to the lack of knowledge of the structure of the university and also due to the trust placed in the sanitation management of the campus. Due to the results obtained, it is convenient to add that this research indicates a need for continuation and development of the theme.
Prevalence of severe neurological damage in patients admitted to an intensive care unit
Keywords: Questionário; Meio ambiente; Saneamento básico; Qualidade de água; Esgoto; Environment; Quiz; Sanitation; Water quality; Sewer; Ciências da Natureza; Natural sciences; CNPQ::CIENCIAS EXATAS E DA TERRA